Will all autonomous cars cooperate? Brands' strategic interactions under dynamic congestion - Xiaojuan Yu; Vincent van den Berg; Erik Verhoef; ZhiChun Li (Tinbergen Institute, 2022)
Autonomous cars allow safe driving with a smaller headway than that required for normal human-driven cars, thereby potentially improving road capacity. To attain this capacity benefit, cooperation among autonomous cars is vital. However, the future market may have multiple car brands and the incentive for them to cooperate is unknown. This paper investigates the competition and cooperation between multiple car brands that, may provide both autonomous and normal vehicles. We develop a two-stage game-theoretic model to investigate brands' strategic interactions and evaluate, from both policy and organizational perspectives, the implications of their cooperation incentives and pricing competition. We compare four market structures: duopoly competition, perfect competition, a public welfare-maximizing monopoly, and a private profit-maximizing monopoly. Various parameters are evaluated, including factors such as the capacity benefits from cooperation, cooperation cost and price elasticity. This evaluation provides policy insights into actions that could be considered by regulators and organizations for the operation of autonomous cars.
Keywords: D21; R41; D43; 330; Autonomous cars; Cooperation strategy; Duopoly competition; Game theory; Regulatory policy